2019
DOI: 10.9770/jesi.2019.6.4(20)
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development of Industry 4.0: the case of high-tech products system design

Abstract: Modern production of high-tech products is characterized by the transition from the traditional design paradigm to the new paradigm of designing a holistic unified set of products. In this regard, the process of designing high-tech products needed to be allocated into a separate typethe system design. Its main methodological provisions are presented in the study. The result of the generalization was the developed system design model, which included the engineering design and process design stages, a method for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The experience of the first three industrial revolutions has shown that technology has a major impact on the labor market, in some areas leading to the disappearance of jobs, and in others to the emergence of completely new occupations and business opportunities [52,53]. The possible consequences of the digitalization of the economy for the creation and disappearance of jobs differ depending on the time frame considered.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of the first three industrial revolutions has shown that technology has a major impact on the labor market, in some areas leading to the disappearance of jobs, and in others to the emergence of completely new occupations and business opportunities [52,53]. The possible consequences of the digitalization of the economy for the creation and disappearance of jobs differ depending on the time frame considered.…”
Section: Discussionmentioning
confidence: 99%
“…The element connecting the different definitions is the integration of people, machines and advanced communication and information technologies, enabling real-time interaction between the key components of an enterprise (manufacturing or service), sector and economy (Młody and Weinert, 2020). 4.0 technologies belong to an open set because of the combinations of solutions and their derivatives permanently developed by manufacturers and users (Batkovskiy et al, 2019).…”
Section: The Concept Of Industry 40mentioning
confidence: 99%
“…Nowadays, the term Industry 4.0, referring to the Fourth Industrial Revolution, with which the digital transformation of the production (Lasi et al, 2014;Prause & Atari, 2017;Batkovskiy et al, 2019;Nagy et al, 2018), refers to the widely accepted concept of the development, but with pressure on the development and also vertical and horizontal integration of small and medium organizations orientated at the technology in the processing industry.…”
Section: Introductionmentioning
confidence: 99%